PECULIARITIES OF AUTONOMOUS REGULATION IN THE PATIENTS WITH SYNCOPE LIVING IN AN INDUSTRIAL CITY - Мартынов, Илья Дмитриевич; Флейшман, Арнольд Наумович (Medicine in Kuzbass, 2017)
Subject. Changes in heart rate variability and systemic hemodynamics in orthostasis in the patients with neurogenic syncope living in an industrial city.Objective. To reveal disturbances of autonomous regulation in the patients with syncope at a young age for early conducting pathophysiologically substantiated therapeutic and preventive measures.Methods. In the young patients with neurogenic syncope who are the residents of Novokuznetsk spectral, statistical and non-linear indices of heart rate variability were determined at the stages of an active orthostatic test. Their dynamics in the sample was assessed taking into account the changes in the indices of systemic hemodynamics and data obtained in the control group.Results. In the residents of an industrial city, the disturbance of sympathetic regulation was determined already at a young age, increasing the risk of early development of cardiovascular diseases. Changes in the power of various parameters of the spectrum of heart rate variability during an orthostatic test make it possible to evaluate compensatory mechanisms for maintaining an adequate level of systemic circulation.Conclusions. Taking into account the changes in the spectral indices of heart rate variability during an active orthostatic test, a pathogenetic approach to the early detection, treatment and prevention of cardiovascular diseases is possible.
Keywords: syncope; autonomous regulation; heart rate variability